Continuous heterogeneously catalyzed oxidation of benzyl alcohol using a tube-in-tube membrane microreactor - Wu, Gaowei; Constantinou, Achilleas; Cao, Enhong; Kuhn, Simon; Morad, Moataz; Sankar, Meenakshisundaram; Bethell, Donald; Hutchings, Graham J.; Gavriilidis, Asterios (My University, 2015)
A Teflon AF-2400 tube-in-tube microreactor is investigated for the continuous, solvent-free, catalytic oxidation of benzyl alcohol with oxygen. The semipermeable Teflon AF-2400 tube acts as the interface between the gaseous oxidant and the liquid substrate. Because of the inherent safety of this contacting method, the use of pure oxygen is possible. The semipermeable tube was packed with 1 wt % Au–Pd/TiO2 catalyst particles and placed inside a PTFE tube to provide an annular region which was pressurized with pure oxygen. This design allowed continuous penetration of oxygen through the inner tube during the reaction, resulting in higher oxygen concentration in the catalyst bed and significantly improved conversion compared to a reactor operating with an oxygen presaturated feed. The amount of oxygen available for reaction in the tube-in-tube microreactor was 2 orders of magnitude higher than that in a nonpermeable reactor with oxygen presaturated feed. The semipermeable tube reactor performance in terms of both conversion and selectivity was enhanced by increasing the gas pressure, the catalyst contact time and by dilution of the catalyst. The highest conversion of benzyl alcohol obtained for the range of conditions investigated was 44.1%, with 73.0% selectivity to benzaldehyde, at 120 °C; catalyst contact time, 115 gcat·s/galcohol; and catalyst dilution factor, 4.
Keywords: Alcohols; Catalysts; Oxygen; Microreactors; Pharmaceuticals